2020
DOI: 10.1172/jci135922
|View full text |Cite
|
Sign up to set email alerts
|

BET bromodomain inhibition attenuates cardiac phenotype in myocyte-specific lamin A/C–deficient mice

Abstract: Mutation in the LMNA gene, encoding lamin A/C, causes a diverse group of diseases called laminopathies. Cardiac involvement is the major cause of death and manifests as dilated cardiomyopathy, heart failure, arrhythmias, and sudden death. There is no specific therapy for LMNA-associated cardiomyopathy. We report that deletion of Lmna in cardiomyocytes in mice leads to severe cardiac dysfunction, conduction defect, ventricular arrhythmias, fibrosis, apoptosis, and premature death within 4 weeks. The phenotype i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 68 publications
9
59
0
Order By: Relevance
“…Can BET bromodomain inhibition ever be a viable therapy for human HF? Observations in preclinical models of acquired and heritable HF support that BET bromodomain inhibition can have broad therapeutic benefit (3,(7)(8)(9)17), possibly via modulating gene expression in multiple cardiac cellular compartments. While BET bromodomain inhibitors are currently being tested in cancer clinical trials (18), their ontarget toxicities in extracardiac tissues may not permit a tractable therapeutic index for chronic disease applications, such as HF.…”
Section: Translational Potential For Human Hfmentioning
confidence: 98%
See 4 more Smart Citations
“…Can BET bromodomain inhibition ever be a viable therapy for human HF? Observations in preclinical models of acquired and heritable HF support that BET bromodomain inhibition can have broad therapeutic benefit (3,(7)(8)(9)17), possibly via modulating gene expression in multiple cardiac cellular compartments. While BET bromodomain inhibitors are currently being tested in cancer clinical trials (18), their ontarget toxicities in extracardiac tissues may not permit a tractable therapeutic index for chronic disease applications, such as HF.…”
Section: Translational Potential For Human Hfmentioning
confidence: 98%
“…The researchers found that Lmna-cKO mice had 100% mortality by 4 weeks of age, preceded by severe cardiac dilation, contractile dysfunction, fibrosis, and cardiac rhythm disturbances that began after 2 weeks of age. Lmna haploinsufficiency caused a milder form of DCM, suggesting dosage sensitivity (3). These phenotypes are observed in patients with LMNA-associated DCM, suggesting cardiomyocyte-specific Lmna loss can trigger major cardiac manifestations of laminopathy.…”
mentioning
confidence: 91%
See 3 more Smart Citations